Bridge performance indicators based on traffic load monitoring - Mandić Ivanković, Ana; Skokandić, Dominik; Žnidarič, Aleš; Kreslin, Maja (Structure and infrastructure engineering, 2019)
The assessment of the existing road bridges as a part of bridge management networks has been a subject of several European research projects and actions in the last few decades. Bridge management includes a series of activities, interconnected in order to achieve optimal balancing of required costs, potential risks and overall bridge performance. This paper discusses a valuable link between a specific indicator (traffic load information calculated using Bridge Weigh-in-Motion measurement data) and the corresponding structural performance (reliability of existing bridge). It is shown that implementation of weigh-in-motion measurements in the probabilistic assessment of existing road bridges can reveal hidden bridge reserves and predict bridge reliability development over the required lifetime. Consequently, such approach can yield an unrestricted use of the bridge over a much longer remaining service life. Broader advantages lie in an improved road network management, road bridges in particular, and in a more sustainable development of infrastructure network and greater satisfaction of road users and owners.